Measuring Li+ Inventory Losses in LiCoO2/Graphite Cells Using Raman Microscopy. Issue 6 (25th March 2016) - Snyder, Chelsea; Apblett, Christopher; Grillet, Anne; Beechem, Thomas; Duquette, David
Abstract : The contribution from loss of Li + inventory to capacity fade is described for slow rates (C/10) and long-term cycling (up to 80 cycles). It was found through electrochemical testing and ex-situ Raman analysis that at these slow rates, the entirety of capacity loss up to 80 cycles can be explained by loss of Li + inventory in the cell. The Raman spectrum of LiCoO2 is sensitive to the state of lithiation and can therefore be leveraged to quantify the state of lithiation for individual particles. With these Raman derived estimates, the lithiation state of the cathode in the discharged state is compared to electrochemical data as a function of cycle number. High correlation is found between Raman quantifications of cycleable lithium and the capacity fade. Additionally, the linear relationship between discharge capacity and cell overpotential suggests that the loss of capacity stems from an impedance rise of the electrodes, which based on Li inventory losses, is caused by SEI formation and repair.